The Impact of Increasing Toll Shop Automation on Income Tax with Vehicle Volume as a Moderatting Variable - Irma Yunita; Enjat Sudrajat (Enrichment : Journal of Management, 2022)
The purpose of this study was to determine the impact of increasing the automation of toll booths on income tax with vehicle volume as a moderating variable. This research method uses the Sem PlS 3.0 method with secondary data obtained from the annual hassle of PT. Jasa Marga in 2009-2018. The result of the research is that automatic toll booths have a significant effect on income tax and vehicle volume while vehicle volume on income tax has no effect.